Cocaine-Induced Acute Interstitial Nephritis: A Comparative Review of 7 Cases. (June 2020) - Inayat, Faisal; Bokhari, Syed Rizwan A.; Roberts, Lisa; Rosen, Raquel M.
Acute interstitial nephritis is a well-known cause of acute kidney injury, but its association with cocaine use is extremely rare. In this article, we chronicle the case of a patient who developed acute interstitial nephritis secondary to cocaine insufflation. Furthermore, we conducted a systematic literature search of MEDLINE, Cochrane, Embase, and Scopus databases regarding cocaine-induced acute interstitial nephritis. A comprehensive review of the search results yielded a total of 7 case reports only. The data on patient characteristics, clinical features, biochemical profiles, treatment, and outcomes were collected and analyzed. This paper illustrates that acute interstitial nephritis may be added to the list of differentials in patients with acute kidney injury and a history of cocaine use. The therapeutic approach for cocaine-related kidney disease may be different than other etiologies responsible for acute renal insult. Prompt recognition of this entity is crucial because such patients may ultimately develop severe deterioration in renal function.